Systemic Sclerosis in Zimbabwe: Autoantibody Biomarkers, Clinical, and Laboratory Correlates - Sibanda, Elopy N.; Dube, Yvonne; Chakawa, Mazvita; Mduluza, Takafira; Mutapi, Francisca (Frontiers in Immunology, 2021)
Abstract Introduction: Systemic sclerosis (SScl) is an autoimmune disease whose prevalence is rarely reported in Africa. Autoantibodies are the biomarkers of the condition, precede overt disease and determine disease phenotypes. SSc specific autoantibodies also vary between racial groupings. Objective: To investigate the clinical and laboratory characteristics of Zimbabwean patients who were reactive SSc specific autoantibodies. Materials and Method: 240 patients, 173 of them female with SSc specific autoantibodies were included. Autoantibodies were detected by indirect immunofluorescence microscopy and immunoblotting using a panel of 13 SScl (Euroimmun Ag., Germany). Demographic, clinical and laboratory parameters relevant to the monitoring of SScl were captured. These included pulmonary function tests, haematology, clinical chemistry, serology and thyroid function tests. Allergy skin prick tests (SPT) to inhalant and food allergen sources were conducted when indicated. Results: All the 240 patients (median age was 36 years) expressed SSc specific autoantibodies. 86% were Black, 11% White and 3% Asian and a fifth (20%) were younger than 16 years. Eleven (4.6%) fulfilled the ACR/EULAR classification of SSc. Clinically they had limited cutaneous (n=6) diffuse cutaneous (n=3) and SScl/inflammatory myopathy overlap (n=2). The most frequently detected antibodies anti-RNA polymerase III (RNAP) 55%, anti-Th/To (28%) anti-RNAP 11 (22%), anti-CENPB (18%) and anti-Scl-70/ATA (13%). Racial variations in the expression of these antibodies were apparent between Black, White and Asian patients. The majority (95%), who did not fulfil the ARA/EULAR criteria were symptomatic. Raynauds' Phenomenon was documented in 24%. Respiratory symptoms included coughing, dyspnoea and wheezing. There was a restrictive ventilatory defect with increased FEV1/FVC ratio. Pruritus, urticaria and skin depigmentation were the main cutaneous features while constipation, bloating, GERD and abdominal pain dominated GI symptoms. Mean blood pressure readings while normal varied with biomarkers. Haematology and biochemistry parameters were within normal reference ranges. Conclusion: The expression of SSc specific autoantibodies is common and associated with known SSc symptoms. The types and frequency of autoantibodies varied with racial groupings. A fifth of the patients were children below the age of 16 years.